Análisis de las salvaguardias en barras de acero inoxidable y su impacto en las importaciones del sector ferretero de la zona norte de Guayaquil - Gordillo Guamán, Ingrid Nataly (2016)
This research aimed to analyze the protective measures in foreign trade imposed by the Ecuadorian government to its imports, in this case of stainless steel bars and their impact on importers of it in the Guayaquil Canton. Methodologically was applied the deductive, exploratory with a quantitative design. The independent variable was a safeguard on imports of stainless steel and dependent was the sales of importers of steel Guayaquil……